(untitled) (Proceedings of International Conference on Special Education, 2019)
This case study explores, examines and understands the factors that motivate deaf /hearing impaired individuals to achieve success and learn the main problems faced in the pursuit of further success and how they overcome such problems. This case study is conducted on two deaf individuals who have lost their hearing before acquiring language, and career in the teaching profession in the state of Penang. Six teachers from the deaf school and 6 deaf pupils were interviewed. Qualitative data collected through interviews, case history, documentary sources and photographs. The findings showed that environmental factors, intrinsic and cognitive development are equally important in moving the deaf individual to achieve the dream of success.